Study Protocol Modeling Evoked Pain in Older African Americans With Knee Osteoarthritis. Issue 5 (September 2021) - Booker, Staja Q.; Starkweather, Angela; Manini, Todd M.; Staud, Roland; Fillingim, Roger B.
Abstract : Background: African American (AA) older adults with knee osteoarthritis experience more severe chronic pain and advanced physical disability. One of the most prominent stimuli that provokes knee pain is movement. Research suggests that, compared to Whites, AAs report significantly higher movement-evoked pain (MEP) in the knee. However, little is known about the biopsychosocial–behavioral mechanisms underlying MEP. Objectives: The aim of the study was to present a study protocol to (a) characterize the biopsychosocial–behavioral mechanisms that predict MEP in AAs with knee osteoarthritis and (b) develop a targeted, mechanism-based self-management intervention to reduce MEP and maximize movement. Methods: An observational, mixed-methods cohort study will enroll 90 AA/Black adults (ages 55–90 years) to understand intraindividual and interindividual effects on MEP. Participants will complete assessments of MEP, function and gait, biopsychosocial–behavioral questionnaires, quantitative sensory testing, and 7-day ecological momentary assessments of pain and related symptoms. For the qualitative phase, focus groups will be conducted to co-construct a mechanism-based pain self-management intervention. Results: We will develop phenotypes of MEP based on biopsychosocial–behavioral predictors and correlate measures of MEP with function. Our central hypothesis is that higher levels of MEP will predict lower self-reported function and poorer performance on functional tasks and that multiple biopsychosocial and behavioral factors will be associated with MEP and function. Predictors may serve as risk or protective factors for MEP and physical function. In targeting the biopsychosocial–behavioral mechanisms of MEP, we anticipate that older AAs may request that intervention components include culturally tailored self-management education, movement/physical activity training, treatment decision-making skills, coaching, spirituality, and social/kinship support. Conclusion: Osteoarthritis is now the single most common cause of disability, mobility limitations, and persistent pain in older adults—especially AA older adults. To our knowledge, this will be the first study to systematically phenotype MEP in an older racial minority population with knee osteoarthritis and will be relevant for reducing knee pain and improving function.